Road lighting for pedestrians: Effects of luminaire position on the detection of raised and lowered trip hazards. (January 2020) - Fotios, S; Mao, Y; Uttley, J; Cheal, C
Previous work investigating how lighting enhances peripheral detection for pedestrians has tended to consider only raised hazards and lighting from a directly overhead source. An experiment was conducted to determine the extent to which variations in these parameters would influence the recommendations for optimal lighting. The results did not suggest a difference in the detection of raised and lowered trip hazards of the same change in vertical height relative to ground level. The results suggest that variation in light source position relative to the target does have a significant effect: To establish the implication of this requires further work to investigate detection under the least-favourable spatial arrangement.